A disaster politicised: The hazardous chemical incident in East Palestine, Ohio - Joel Keep; David Heslop (University of New South Wales, 2023)
The recent derailment of a freight train in the U.S. state of Ohio unleashed hazardous chemicals - and poisonous divisions in American politics.